EFEKTIVITAS PERSUASIF MELALUI NARASI DAN BUKTI STATISTIK TERHADAP PENGAMBILAN KEPUTUSAN MEMILIH PRODUK HANDPHONE - Alwinansyah Farnas; Gumgum Gumelar (Journal of Research and Measurement in Psychology, 2017)
The aim of this study was to determine whether there is a difference to the effectiveness of persuasion toward narrative and statistical evidence in making decisions selecting mobile products in adolescents. The study was conducted from September to January 2013. This study uses a method of controlled experimental studies labolatory. Analysis using t-test of the difference independent test samples from the test results obtained values F = 1461, p = 0231> 0.05 (not significant), meaning that there is no difference in the effectiveness of persuasion through narrative and statistical evidence on decision making in adolescents choose mobile products . Comparison of average (mean) persuasive narrative and persuasive statistical evidence obtained mean value 62.12 for the narrative and the mean value for the statistical proof of 60.06. Based on the results of this analysis rejected the hypothesis that there is no difference in the effectiveness of persuasion through narrative and statistical evidence for making decisions on choosing mobile products in teens. The implication of this research is to use both types of persuasive in influencing a person's decision-making in the absence of differences in effectiveness between the two.